48 administrative and academic staff in UMPSA Management and Professional Group promoted - Safriza, Baharuddin (UMPSA, 2025)
PEKAN, 23 March 2025 – A total of 48 administrative and academic staff in the Management and Professional Group of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received their promotion letters from the Vice-Chancellor, Professor Dr. Yatimah Alias, in a ceremony held at the Senate Hall, Chancellery Tun Abdul Razak.